The main reasons of conflicts between adolescents in the multicultural class and their prevention - Khukhlaeva, O.V. (Socialʹnaâ Psihologiâ i Obŝestvo, 2017)
The conflict interaction in the adolescent environment, mainly in the context of intercultural interaction, is considered in the article on the basis of theoretical analysis. The relationship between conflict in adolescence and the overcoming of adolescent crisis is described, as well as the conflict was correlated with other age characteristics. A special emphasis is placed on intergroup conflicts. An additional specificity of conflicts in school classes with mixed cultural composition is discussed. An analysis of the specifics of the conflict interaction in connection with the measurement of cultures by G. Hofstede was carried out (individualism-collectivism, power distance, masculinity-femininity and avoidance of uncertainty). The conclusion about the greater urgency of potential contradictions is being made if there are teenagers belonging to widely differing cultures in the school class. The role of laughter culture as manifestations of antipodes in game form for the prevention and correction of conflicts in a adolescent multicultural environment is shown. В статье, на основе теоретического анализа, рассматривается конфликтное взаимодействие в подростковой среде, преимущественно в контексте межкультурного взаимодействия. Описана взаимосвязь между конфликтностью в подростковой среде и прохождением подросткового кризиса, а также произведено соотнесение конфликтности с иными возрастными особенностями. Отдельный акцент сделан на межгрупповых конфликтах. Обсуждается дополнительная специфика конфликтов в классах со смешанным культурным составом. Проведен анализ специфики конфликтного взаимодействия в связи с измерениями культур по Г. Хофстеде (индивидуализмом-коллективизмом, дистанцией власти, маскулинностью-феминностью и избеганием неопределенности). Делается вывод о большей остроте потенциальных противоречий, если в классе есть подростки, принадлежащие к значительно различающимся культурам. Показана роль смеховой культуры как проявления антиповедения в игровой форме, для профилактики и коррекции конфликтов в подростковой поликультурной среде.